(untitled) (Journal of Management and Business Education, 2018)
The editorial of this second issue of the Journal of Management and Business Education (JMBE) highlights the importance of contributing from the academy with scientific research on the educational process; both in general, and in particular in the specific field of higher education in business management. To do this, the impetus that the research on the learning teaching process, the Scholarship of Teaching and Learning (SoTL), and its dissemination through publications such as this one, the JMBE is showing in the current international academic landscape. The research related to the commitment of the university student, the Student Engagement, is also presented in all its dimensions; glimpsing topics of increasing interest in the same. On the other hand, this editorial is the presentation of the content of the articles that make up the second issue of the magazine. Finalizing with thanks to all participants of the project that has come true.